2020
DOI: 10.20396/etd.v22i1.8655410
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação da eficácia de um programa de compreensão da leitura oral dialógica por criança com autismo

Abstract: Os prejuízos nos níveis de compreensão leitora de educandos diagnosticados com Transtorno do Espectro Autista (TEA) aparecem documentados em pesquisas científicas. Nesse cenário, o desenvolvimento de programas de intervenção que possam remediar, precocemente, esses déficits são essenciais.  O presente estudo tem como objetivo avaliar a eficácia de uma adaptação do programa de intervenção leitora, denominado Reading to Engage Children with Autism in Language and Learning (RECALL). Esse programa incorpora prátic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 30 publications
(17 reference statements)
0
2
0
Order By: Relevance
“…The literature has shown that interactive shared storybook reading is an evidence-based practice that enhances the language and literacy skills of typically developing children (National Early Literacy Panel [NELP], 2009) (Lonigan et al,2009) as well as those with developmental disabilities, such as autism spectrum disorder (ASD) (Whalon et al, 2015). These investigations have further highlighted the benefits of conducting intervention in the natural setting, involving parents as readers (Whitehurst et al, 1988;Westerveld et al, 2021;Walter, 2017;Whalon et al, 2016;Lo & Shum, 2021). The home environment, for instance, provides various opportunities for children to learn in meaningful contexts.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The literature has shown that interactive shared storybook reading is an evidence-based practice that enhances the language and literacy skills of typically developing children (National Early Literacy Panel [NELP], 2009) (Lonigan et al,2009) as well as those with developmental disabilities, such as autism spectrum disorder (ASD) (Whalon et al, 2015). These investigations have further highlighted the benefits of conducting intervention in the natural setting, involving parents as readers (Whitehurst et al, 1988;Westerveld et al, 2021;Walter, 2017;Whalon et al, 2016;Lo & Shum, 2021). The home environment, for instance, provides various opportunities for children to learn in meaningful contexts.…”
Section: Introductionmentioning
confidence: 99%
“…From the six studies that have used the RECALL protocol, published in the research literature (Whalon et al, 2015;Whalon et al, 2016;Walter & Nunes, 2020;Jackson & Hanline, 2020;Lo & Shum, 2020;Nunes et al, 2021), three involved parents as intervention agents (Whalon et al, 2016;Walter & Nunes, 2020;Lo & Shum, 2020). The dependent variables evaluated in these investigations included the child's spontaneous response frequency, the correct response to questions in the story, and turn-taking.…”
Section: Introductionmentioning
confidence: 99%